U-47700: An Emerging Threat - Alzghari, Saeed K (Cureus, 2017)
Illicit opioid use continues to be an ever-growing problem in the United States. The rise of synthetic opioids is an emerging threat that is beginning to draw attention over the past few years. Herein, we present an overview of the rise of a synthetic opioid known as U-47700. We describe U-47700's history, legal status, ease of obtainment, consequences of its use, and a proposal to increase the awareness of this synthetic opioid.